2009
DOI: 10.1152/jn.90783.2008
|View full text |Cite
|
Sign up to set email alerts
|

Active Touch Sensing in the Rat: Anticipatory and Regulatory Control of Whisker Movements During Surface Exploration

Abstract: Animals actively regulate the position and movement of their sensory systems to boost the quality and quantity of the sensory information they obtain. The rat vibrissal system is recognized to be an important model system in which to investigate such "active sensing" capabilities. The current study used high-speed video analysis to investigate whisker movements in untrained, freely moving rats encountering unexpected, vertical surfaces. A prominent feature of rat vibrissal movement is the repeated posterior-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
273
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 196 publications
(290 citation statements)
references
References 30 publications
15
273
2
Order By: Relevance
“…This control is afforded by a specialized musculature, which includes dedicated muscles, one per whisker, that are intrinsic to the whisker pad, as well as muscles external to the pad that can move all of the whiskers together by shifting the pad or by transforming its shape [3,[6][7][8]. The characteristic pattern of rat whisker movement, and also its principal component when viewed from above [9], is for all of the macrovibrissae (around 35 on each side of the snout) to move forward together (protract), and then be pulled back together (retract). This sweeping or scanning motion, known as 'whisking', is repeated successively, many times per second, for periods lasting several seconds at a time [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This control is afforded by a specialized musculature, which includes dedicated muscles, one per whisker, that are intrinsic to the whisker pad, as well as muscles external to the pad that can move all of the whiskers together by shifting the pad or by transforming its shape [3,[6][7][8]. The characteristic pattern of rat whisker movement, and also its principal component when viewed from above [9], is for all of the macrovibrissae (around 35 on each side of the snout) to move forward together (protract), and then be pulled back together (retract). This sweeping or scanning motion, known as 'whisking', is repeated successively, many times per second, for periods lasting several seconds at a time [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These observations motivate the proposal that whisking is a form of active sensing according to the definition used in this theme issue. That is, that animals whisk, and modulate their whisking behaviour in specific ways, in order to boost the acquisition of task-relevant sensory information [9,16]. To fully evaluate this hypothesis, two further steps are needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This essentially limited Whiskerbot to exploring vertical surfaces near ground level. Meanwhile, our research with rats increasingly demonstrated the importance of movements of the head and neck in positioning the vibrissal array in whiskered animals [36]. To overcome these limitations, and others, we therefore developed a completely new whiskered robot platform, SCRATCHbot [14,42] (figure 1b).…”
Section: Introductionmentioning
confidence: 99%